SÍNTESE E ESTUDOS ÓPTICOS DE VIDROS TELURITOS DOPADOS COM Nd3+ PELO MÉTODO FUSÃO/RESFRIAMENTO - DEVECCHI, Marcos Renan de Freitas; LANGARO, Ana Paula; ANDRADE, Luis Humberto da Cunha (ANAIS DO ENIC, 2020)
-